“La calidad del servicio al cliente como ventaja competitiva de los comerciantes del sector la Bahía del cantón La Maná. - Casillas Pilaguano, Ronny Francisco (2022)
Currently, quality is a strategic element of competitive advantage which is oriented to the anticipation of needs, expectations, loyalty, and permanence of the clients. The research project emerged from the ignorance of the quality of customer service provided by the owners of the stores in La Bahía sector. The objective is to analyze the quality of customer service and the competitive advantages of traders in La Bahía sector in La Maná canton. For this purpose, the bibliographic research was used to collect information from books, journals, scientific articles, thesis, and websites by different authors to support the theoretical bases. Also, the theoretical method to differentiate and make a deeper research on the variables, the deductive method to deduce the important aspects to the problem about the quality of the service, the synthetic and analytical method to classify and analyze the obtained information in the applied surveys to traders and customers. The results indicated that the 100% of the quality of service in La Bahía sector is deficient, while 4.29% of businesses have low competitiveness, 40% of businesses have medium competitiveness, and 55.71% of businesses have high competitiveness. According to the results, it can be said that there is not independence of variables, that the one depends on the other, so it was proceeded to design a proposal that has as a general objective to elaborate a strategy of improvement in relationship to the quality of customer service for the optimization of competitive advantages of traders in La Bahía sector in La Maná canton. In addition, to improve the following aspects in the quality of service: tangibility, reliability, responsiveness, security, and empathy; and in the competitive advantages: quality of service, price, advertising, flexibility, attitudes, and availability. It included an organizational design and a training strategy for traders. With this research, the students of the TUC will be benefited, owners of the stores of La Bahía, customers, and state entities for the collection of taxes.